The Evaluationof Mustahiq Training Effectiveness in Rumah Gemilang Indonesia (RGI) for the 16th Generation to Increase Work Readiness - Fauziyah Rahmi Adilah; Muhammad Findi; Khalifah Muhamad Ali (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
Indonesia is the fourth largest country in the world in terms of population size. However, the potential of large amounts of Indonesian human resources cannot be optimized due to the continuing high number of unemployed people. Rumah Gemilang Indonesia (RGI) is a program run by the Al-Azhar National Amil Zakat Institute, focusing on the eradication of productive-age unemployment. The purpose of this research is to examine the implementation of the mustahiq training organized by RGI and to evaluate the running of mustahiq training at the reaction level, learning level, behavioral level, and results level. The methods used to process and analyze the data are descriptive analysis and paired data t-test. The result shows that the mustahiq training organized by RGI has been effective. At the reaction level, the respondents were quite contented with the training. The result of the paired data t-test at the learning level shows that there is a significant difference inmustahiqs’ competence before and after the training. At the behavioral level, on average, the respondents always apply the training materials to their job. At the results level, RGI’s vision to increase the level of work readiness has been achieved. Keyword: Kirkpatrick model, paired data t-test, productive zakat, training effectiveness, unemployment measure